"Your sister growes rich by her great trade": Catherine Nicks's Intimate Economy. Issue 3 (December 2022) - Laursen Brock, Aske
Abstract: "Catherine Nicks's Intimate Economy" introduces an intimate network that spanned Europe and Asia in the late seventeenth and early eighteenth centuries, underlining how women created opportunities for themselves and their extended network. Using the case study of Catherine Nicks, the article examines how a trading company's network, in spite of the company's desire for impermeable monopolies, lent itself to women and others who could form durable intimate networks underneath the larger corporate umbrella for personal and familial economic gains. It questions how the early modern maritime and global economy worked while also examining the nature of company monopolies.